Seriously, Norman! [compact disc, unabridged] - Raschka, Christopher (Scholastic Audiobooks, 2011)
Why are grown-ups so insane? That's the question Leonard, Norman, Anna and Emma try to answer with the help of Norman's tutor, Balthazar Birdsong.